Value return predictability across asset classes and commonalities in risk premia - Baba-Yara, Fahiz (2019)
We show that returns to value strategies in individual equities, industries, commodities, currencies, global government bonds, and global stock indexes are predictable in the time series by their respective value spreads. In all these asset classes, expected value returns vary by at least as much as their unconditional level. A single common component of the value spreads captures about two–thirds of value return predictability and the remainder is asset class–specific. We argue that common variation in value premia is consistent with rationally time–varying expected returns, because (i) common value is closely associated with standard proxies for risk premia, such as the dividend yield, intermediary leverage, and illiquidity, and (ii) value premia are globally high in bad times.